2018
DOI: 10.1136/bcr-2018-013842
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of a totally occluded aneurysm after treatment with a pipeline embolization device

Abstract: Treatment with a pipeline embolization device (PED) is widely accepted as an excellent option for patients harboring giant, wide neck, saccular intracranial aneurysms. It has been shown to be safe and very effective. We describe a previously unreported case of a large middle cerebral artery aneurysm, related to the carotid tip, that was treated with a PED and coils. The 6 month follow-up angiogram demonstrated complete occlusion of the aneurysm. However, the 9 month angiogram revealed recurrent filling of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…A recent case report showed angiographic evidence of aneurysm recurrence at 9-month follow-up despite complete occlusion on angiography at the 6-month follow-up post-treatment with a PED FD and coils. 49 Zhang et al have also shown recurrence of a completely occluded aneurysm treated with a Tubridge FD at the 2-year followup. 51 FD treatment can also delay aneurysm rupture through aneurysm wall thrombus-associated autolysis.…”
Section: Mechanism: Endothelializationmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent case report showed angiographic evidence of aneurysm recurrence at 9-month follow-up despite complete occlusion on angiography at the 6-month follow-up post-treatment with a PED FD and coils. 49 Zhang et al have also shown recurrence of a completely occluded aneurysm treated with a Tubridge FD at the 2-year followup. 51 FD treatment can also delay aneurysm rupture through aneurysm wall thrombus-associated autolysis.…”
Section: Mechanism: Endothelializationmentioning
confidence: 97%
“…45,46 FD treatment failure is usually attributed to inadequate coverage of the aneurysm, presence of a pre-existing stent, presence of an incorporated branch, or endoleak analogous to that seen in endovascular abdominal aortic aneurysm repair. 49,50 Dai et al reported on a basilar tip aneurysm treated with a PED FD that showed complete occlusion on angiography at 4 months, with subsequent recurrence at 12 months. Other mechanisms that could explain recurrence are branch vessel runoff or improper endothelialization and thrombus formation leading to aneurysm recurrence and delayed rupture despite angiographic evidence of complete occlusion.…”
Section: Mechanism: Endothelializationmentioning
confidence: 99%
See 3 more Smart Citations